Mediation as a Factor Strengthening the Communicative Aspect of Law - Kalisz, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
When reviewing contemporary concepts of law, it is easy to notice that many of them emphasise the role of communication and dialogue in law. This paper is an attempt to link the philosophical aspect with legal practice, picturing both the basic ontological concepts based on the communicative aspect and the mediation as a form of dialogue in law application process. The aim is to draw attention to the correspondence between the mediation and deliberative democracy in the multi-centric legal reality. The conclusion indicates that the professionalisation of the profession of mediator shall help in such a process.